2021
DOI: 10.1111/jonm.13474
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and psychological implications for healthcare professionals in disasters or mass casualties: A systematic review

Abstract: Aim: To synthesize and describe the emotional and psychological implications for healthcare professionals who provided care in a mass casualty incident or disaster. Background:The experience of healthcare providers immersed in the actual uncertainty of an ongoing disaster is real, challenging, complex and strongly connected with emotions. Identifying these implications for healthcare professionals is essential for developing strategies to help these professionals deliver high-quality care.Evaluation: A systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…As a result, effective psychological first-aid training is critical [ 25 26 ]. According to a recent systematic review, cognitive behavioral therapy, psychoeducation, or meditation may assist nurses in overcoming their lack of emotional preparedness [ 27 ]. Furthermore, professional preparedness is essential for effective disaster response.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, effective psychological first-aid training is critical [ 25 26 ]. According to a recent systematic review, cognitive behavioral therapy, psychoeducation, or meditation may assist nurses in overcoming their lack of emotional preparedness [ 27 ]. Furthermore, professional preparedness is essential for effective disaster response.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of memory recall amongst nurses after disaster events are not found. However, the emotional impact of disasters on nurses is sufficiently documented [49]. For this study, the time from the disaster event to the interview varied.…”
Section: Limitationsmentioning
confidence: 99%
“…Nurses assess and prioritize patients, efficiently allocating resources to provide prompt care to those in critical needs. Additionally, they offer emotional support to survivors, providing reassurance and alleviating anxiety in chaotic circumstances [ 2 ]. With their expertise in psychological first aid and counseling, nurses help victims cope with the psychological aftermath of the disaster [ 3 ].…”
Section: Introductionmentioning
confidence: 99%